The role of modern augmented applications in improving the efficiency of engineering projects - Mandani, Sami Abdullah; Alfareis, Mohammad Jasem (Journal of engineering sciences and information technology, 2023)
The Fourth Industrial Revolution, which began in 2016, was referred to as a new stage in the development of technology. One of the most important innovations that took place during this period was the development of augmented reality, which allows users to interact with virtual objects and images in real life. Due to its transparent capabilities and interactivity, augmented reality is more suitable for engineering than virtual reality. It can help reduce errors and improve the efficiency of engineering projects. This research reviews the different applications of augmented reality in this field. Over the past five years, the construction industry has been one of the most prominent sectors that has invested heavily in the development of augmented reality. Researchers are currently using the technology in various ways, such as in-situ engineering disciplines conflict and collaborative communication. They also use BIMs to create 3D models of structures. Various studies have been carried out on the use of modeling in the field of engineering design. Such as project design, interior decoration, has also been used in the design and construction of smart cities. The study explores the different challenges and applications of augmented reality in the engineering design sector.